2021
DOI: 10.1007/978-981-16-5727-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping COVID-19 in Japan and Greater Tokyo Area, Socio-Spatial and Political Analysis of the Epidemic

Abstract: This chapter provides a political analysis of the COVID-19 crisis management in Japan completed by a socio-spatial analysis during the first three waves of the epidemic. Introducing the infectious diseases legal framework to pinpoint the key notion of "responsibility" allows us to understand coordination among political, scientific, and economic actors, and citizens, at national and local levels, allowing the implementation of various measures applied to each new wave. We then highlight tensions, power relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As an example, the COVID-19 pandemic dynamics in Japan in the summer of 2020, 2021 and 2022 will be investigated in order to estimate the impact of vaccination levels on the numbers of new infections, death, and mortality rates. Some other studies of COVID-19 dynamics in Japan can be found in ( Chen et al., 2021 ; Fukumoto et al., 2021 ; Nesteruk, 2022a ; Nesteruk, 2022b ; Nesteruk, 2022c ; Niwa et al., 2020 ; Sala et al., 2022 ; Shimizu & Negita, 2020 ; Torjesen, 2022 ; Uehara, 2020 ; Yamauchi et al., 2022 ; Yoneoka et al., 2021 ; Ko et al., 2022 ; Kato et al., 2022 ; Zeyu & Takikawa, 2021 ). An example of a user-friendly interface is presented in ( Dong et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the COVID-19 pandemic dynamics in Japan in the summer of 2020, 2021 and 2022 will be investigated in order to estimate the impact of vaccination levels on the numbers of new infections, death, and mortality rates. Some other studies of COVID-19 dynamics in Japan can be found in ( Chen et al., 2021 ; Fukumoto et al., 2021 ; Nesteruk, 2022a ; Nesteruk, 2022b ; Nesteruk, 2022c ; Niwa et al., 2020 ; Sala et al., 2022 ; Shimizu & Negita, 2020 ; Torjesen, 2022 ; Uehara, 2020 ; Yamauchi et al., 2022 ; Yoneoka et al., 2021 ; Ko et al., 2022 ; Kato et al., 2022 ; Zeyu & Takikawa, 2021 ). An example of a user-friendly interface is presented in ( Dong et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%